Neuroglial Axons - Vaquero Crespo, Jesús (Investigación Clínica, 2012)
The author bases ibis work on findings which reveal a morphological similitude between neurons and glial cells and on the existence of neuroglial circuits in order to try to identify funcionally some glial types with neurons of a short axon. This report adds some pictures showing anatomically the axon in neuroglial cells.